BIMBINGAN KELOMPOK DALAM MENINGKATKAN INTERAKSI SOSIAL PADA ANAK TUNA RUNGU DI YAYASAN ADI NUGRAHA BOYOLALI - Insulistyani Fajar Harini (Academic Journal of Psychology and Counseling, 2020)
This research intends to know and describe how the group's guidance in social interaction at Yayasan Adi Nugraha Boyolali. The type of research used is qualitative research. Penelitin sees, observations, collects and interprets the data in the field as it is to then draw conclusions. The subject in this study was the chairman of Yayasan Adi Nugraha Boyolali, 2 guiding teachers and two deaf children. Data collection techniques using interviews and observations. Data analysis methods used are data reduction, data presentation and withdrawal of conclusions. Validity of data using source trianggulation. The results of this study showed that the process of mentoring child groups will be given motivation so that the child is always positive thinking, foster self-confidence and way of interacting socially with normal children. While in the process of implementing group guidance there are 4 stages, namely: the initial stage of the group, the transition phase, the activity stage, the final stage of the group.